A Critique of Speculative Materialism's Critique of Kant's Criticism - Chalabi, Fares (Cosmos and History: The Journal of Natural and Social Philosophy, 2022)
This paper aims at clarifying the Kantian ontological position by confronting the criticisms of Speculative Materialism. The article has then two goals, negatively to show that Speculative Materialism fails to destroy the Kantian critical system, positively to provide a sharper version of Kant’s Critique of Pure Reason thanks to its confrontation with Speculative Materialism. In the following essay, we will oppose the speculative materialist interpretation of Kant to our analysis concerning the following points: the arche-fossil and the meaning of possible experience, the interpretation of the stability of nature and the status of the thing itself, the anti-frequentialist argument and the relation between the contingency of the laws of nature and the stability of the phenomenal order, the possibility to inverse our ignorance of the thing itself into a knowledge of the thing itself, and the validity of the Kantian descriptive analytical method. Such radicalization of Kant and the critique of his critics is required to prevent a hasty overcoming of correlationism which in fact leaves correlationism intact. A first step to overcome correlationism would be then to deploy its full power which will allow us to measure the difficulty of such enterprise and hence prepare for a radical critique of Kantian criticism.